Utilization of Kahoot Learning Games as Interactive Learning Media - Imam Riadi; Sunardi Sunardi; M. Ihya A. Elfatih; Ariful Aziz; Amirul Mumin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The world of education certainly cannot be separated from teaching and learning activities. Educators are required to be able to make the learning atmosphere feel fun and exciting. Educators are required to be able to take advantage of existing learning media, whether it's modules, worksheets, or electronic books to be optimized as learning support tools both in the inside and outside the classroom. Effective, conducive, and creative learning in this modern era has changed the style and process of learning. Outbreak of the covid-19 requires teaching and learning activities to be carried out remotely relying on internet technology. Kahoot is a web-based learning media which in its operation involves educators and students to interact and conduct interactive learning in the form of games, quizzes, surveys, and polls. The use of Kahoot as a learning media is considered appropriate because both students and educators have been confirmed as active internet users. The use of the internet for learning can also brighten the view that the digital world is increasingly sophisticated, educate students to surf the internet wisely, and learning activities teaching is not always monotonous and boring.